Tra verità e inganni. Polifonia apparente e aspetti picareschi nel viaggio dialogato del Lazarillo de Ciegos Caminantes (ENTHYMEMA, 2023)
Among all 18th-century travel writings, there is one work that certainly stands out for giving rise to many debates related to its structure, narration and even authorship: Lazarillo de ciegos caminantes. This essay addresses one of the most fascinating aspects of the text, which is the supposed presence of literary polyphony that actually reveals a unilateral narration articulated by just one true voice. A possible inspiration of the traditional picaresque could have been added to it. The analysis of this combination of elements, between the rigid-monolithic perspective and the hypothetical picaresque influence, is the main topic of the study.